LCART: Lightweight Congestion Aware Reliable Transport Protocol for WSN Targeting Heterogeneous Traffic - Sharif, Atif; Potdar, Vidyasagar; Rathnayaka, Dinusha (Australian National University, 2010)
This paper presents energy ecient transport layer protocol for heterogeneous WSN, named as LCART. LCART fuses the prevalent or reciprocal functionalities of Transport, MAC and Wireless-Physical layers in order to achieve energy eciency and meeting QoS objectives of heterogeneous WSN. LCART intelligently provide congestion control by the simultaneous use of Packet Service Time (TPST), Packet Inter Arrival Time (TPIAT), Buer Occupancy Level (mi) and Channel Loading Threshold limits (Threshold) constraints to formalize new source rate plan for avoiding congestion. LCART achieves packet level reliability by using explicit NACK and parameter entirely being governed by the nature of the trac. LCART has been tested for 24 mote ad-hoctopology and results reveal that it exhibit highest good throughput of 0.3112 Mbps, < 80msec and < 130 msec average End-to-End (E-2-E) packet latency for high and low prioritized packet information, 1.014% average percentage packet drop and overall exhibits energy ecient behavior (lowest per packet communication cost) in comparison to TCP-Westwood+ (TCP-WW+), TCPWestwood (TCP-WW), TCPNewReno and TCPReno.